"One stone and two birds" strategy to treat neovascular age-related macular degeneration by a novel retinoid drug, EYE-101. (February 2023) - Xu, Miao; Shen, Ya-Ming; Han, Xiao-Yan; Liu, Chang; Jiang, Qin; Cao, Xin; Yan, Biao
Abstract: Choroidal neovascularization (CNV) is a typical pathological feature of neovascular age-related macular degeneration and has become a major cause of vision loss in the elderly. Current therapies require repeated intraocular injections of anti-VEGF drugs by inhibiting endothelial angiogenic effects, which is painful and may cause adverse effects on normal vascular and neuronal functions. Herein, we designed a novel retinoid drug, EYE-101, determined its therapeutic effects on CNV, and clarified the anti-angiogenic mechanism. The results show that administration of EYE-101 did not cause obvious cytotoxicity and ocular tissue toxicity at the concentrations less than 5 μM. Topical administration of EYE-101 could reduce choroidal sprouting, suppress laser-induced CNV formation, and decrease pericyte coverages on ocular vessels. Administration of EYE-101 also suppressed endothelial cell proliferation, migration, and tube formation and reduced pericyte proliferation, migration, recruitment towards endothelial cells. EYE-101 exerted its anti-angiogenic effects by targeting endothelial cells and pericytes via antagonizing Wnt/β-catenin signaling and PDGF signaling. Thus, EYE-101 administration may offer an"one stone and two birds" strategy for the prevention and treatment of ocular neovascular disorders. Highlights: EYE-101 has no detectable cytotoxicity and tissue toxicity. EYE-101 suppresses endothelial angiogenic function. EYE-101 suppresses pericyte dysfunction. EYE-101 suppresses choroidal sprouting and choroidal neovascularization. Retinoic acid receptor is the primary cellular target for EYE-101. EYE-101 exerts its anti-angiogenic effects via Wnt signaling and PDGF signaling.